(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Cuscuta australis (C. australis) seed and stem are commonly used as dietary supplements in a maize-meal, “Ogi”, by the local population for the management of male and female reproductive dysfunctions. This study, as a part of on-going efforts, therefore, evaluated and compared the effects of Low Protein-energy (LP) and Normal Protein-energy (NP) diets on the sperm morphology and characteristics of adult Wistar rats orally dosed aqueous extracts of C. australis seed (LPSE and NPSE) and stem (LPST and NPST), 300mg of extract/kg body weight of rat/day, for seven days. The control groups (LPWA and NPWA) received vehicle, water. Live-dead ratio and percentage of sperms with curved tail were significantly decreased (p<0.01) in the NPST relative to the NPWA, LPWA, LPST, NPSE and LPSE. Total abnormal sperm counts, acephalic sperms and tailless head sperms were significantly decreased (p<0.001, p<0.05 and p<0.001, respectively) in the LPST and NPST relative to LPSE, NPSE, LPWA and NPWA. The LPSE, LPST and NPST showed significantly decreased (p<0.05) percentages of sperms with either bent mid-piece or curved mid-piece relative to the LPWA. Significantly decreased (p<0.05) percentage of sperms with curved mid-piece was also observed in the NPSE relative to LPWA. Protein-energy diet significantly influenced (at least p<0.05) the effect of each extract on sperm motility and percentage of sperms with curved tail. Stem extract significantly decreased (p<0.01) the percentages of acephalic sperms and tailless head sperms. Diet-stem extract interaction significantly influenced (p<0.05) live-dead ratio. Our data suggest that orally administered aqueous extracts of C. australis generally enhanced the sperm morphology and characteristics of the male Wistar rat and that the stem extract maintained sperm morphology better than the seed extract. It also showed that the stem extract decreased live-dead ratio and that the efficacy of orally administered aqueous C. australis stem extract may be affected by variations in dietary protein-energy levels.